Study on Designing a Curriculum Suitable for MOOC Platforms Starting Out the Romanian Students' Expectations. (2016) - Bucovetchi, Olga; Stanciu, Radu D.; Simion, Cristina Petronela
Abstract: The educational environment switched the place of the classical classroom into the online environment. Massive Open Online Courses (MOOC) appears to be the easiest way to improve the knowledge and/or the skills as people are able to access the information they are interested in at an academic level. The purpose of the present paper is to identify the degree of attractiveness of such classes hosted by MOOCs (Massive Online Open Classes) platforms in order to design a sample-module of this kind. The main added value and originality of the present work rises from the design of the first Romanian class to be hosted on MOOC platforms. Usually, when designing the content of a class, the starting point is the market need or the previous experience in academic environment related to that topic. In present paper, the UPB (University "POLITEHNICA" of Bucharest) students' expectations were the starting point for designing such class.